Evaluation of grain breakage sensitivity of maize varieties mechanically-harvested by combine harvester - Wang, Yizhou; Li, Lulu; Gao, Shang; Guo, Yanan; Zhang, Guoqiang; Ming, Bo; Xie, Ruizhi; Xue, Jun; Hou, Peng; Wang, Keru; Li, Shaokun (International Journal of Agricultural and Biological Engineering, 2020)
A high grain breakage rate is the main problem that occurs during mechanical maize harvest in China. The breakage sensitivity of different varieties was significantly different, and the breakage resistance is heritable. Therefore, breakage resistant variety screening can help improve the field production efficiency and provide references for breeding work. In this study, 42 varieties of maize were harvested with the same mechanical parameters and the same manipulator on a range of harvest dates at experimental stations in Xinxiang, Henan Province, in 2017 and Changji, Xinjiang Province, in 2018 to determine the sensitivity of grain moisture content on grain breakage rate during machine harvest for different varieties. The integral value of the grain breakage rate curve corresponding to the range of 15% to 30% grain moisture content was used as an index that expressed the sensitivity of maize grains to breakage depending on grain moisture content (BSW). Forty-two varieties were categorized as having weak, intermediate, or strong BSW. Among the same four varieties in the two stations, Lianchuang 825 and Lianchuang 808 were classified as sensitive and fragile varieties, Shandan 650 was classified as an intermediate variety, Zeyu 8911 was divided into weak sensitive and breakage-resistance varieties in Xinxiang and intermediate varieties in Changji. The BSW classification results at the two experimental sites were generally consistent, indicating that breakage sensitivity due to moisture content may be a relatively stable genetic characteristic. This study suggested that the integral method for determining BSW can be used to assess the resistance of different maize varieties to grain breakage during mechanical harvesting. The integral method was used to identify twelve breakage-resistant varieties in Xinxiang Station, and six breakage-resistant varieties in Changji Station. This study provides a method for screening maize varieties that are suited to mechanical grain harvesting and for studying the mechanisms of grain breakage resistance.Keywords: maize, mechanical grain harvest, breakage resistance, integral method, varieties classificationDOI: 10.25165/j.ijabe.20201305.6037Citation: Wang Y Z, Li L L, Gao S, Guo Y N, Zhang G Q, Ming B, et al. Evaluation of grain breakage sensitivity of maize varieties mechanically-harvested by combine harvester. Int J Agric & Biol Eng, 2020; 13(5): 8–16.